PENGARUH PAJAK KENDARAAN BERMOTOR TERHADAP PENDAPATAN PAJAK DAERAH - Nora Januarti Panjaitan; Hengki Mangiring Parulian Simarmata (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
In terms of technological developments today, more and more people have vehicles to run daily activities. Therefore, vehicle taxes become superior in providing income and become a greater source of income than other types of local taxes. The objective of this research is to know the influence of vehicle taxes to local tax revenues at the BERSAMA SAMSAT office of Pematangsiantar. The sample in this research is in the form of vehicle tax revenue of Simalungun Regency report in the period of 2013-2016 at BERSAMA SAMSAT Office of Pematangsiantar since the data in the form of the latest financial statements t so that can be calculated the development and the problem. The data collection method in this research is documentation and observation method. The data analysis method in this study using microsoft excel, that is by simple linear regression test method. The result of this research is that partially vehicle taxes positively influence to local tax revenue of Simalungun regency and Pematangsiantar City with contribution of influence given 99% while the rest 1% is the influence of other factors not examined. Thus the better the acceptance of vehicle taxes, the local tax revenue of Simalungun and Pematangsiantar City will increase.